Penyimpangan dalam Penafsiran Al-Qur’an: Analisis Penafsiran Kelompok Millah Ibrahim - Mohd Farhan bin Md Amin; Maizuddin Maizuddin; Hisyami bin Yazid (TAFSE: Journal of Qur'anic Studies, 2020)
Millah Ibrahim is a group that emerged in Johor and believes that prayer is not an obligation in Islam, they believe in the Day of Judgment, and are trying to unite the teachings of Islam, Christianity, and Judaism so that it has a great impact on the common people. Their opinions are based on the verses of the Qur'an with a distorted understanding. This article tries to examine how the deviations in the interpretation of the Qur'an were carried out by the Millah Ibrahim group and how the impact of these deviations on the people of Johor. The results show that the deviations in interpretation carried out by Millah Ibrahim's group are seen in Surah al-Maidah verse 68, Surah al-Baqarah verse 22, al-Ankabut verse 45, and al-Hijir verse 87. These deviations generally occur because of the lack of fulfillment of the requirements to become a commentator. The impact of these deviations, where the general public in Johor was consumed by the explanations presented by this group. This group explains that what is meant by the Day of Judgment mentioned in the Qur'an is not the day when this world is destroyed and then the jinn and humans are resurrected, but what they mean is the day of religious awakening. Millah Ibrahim merupakan satu kelompok yang muncul di Johor, dan berpandangan bahwa salat bukan kewajiban dalam Islam, mereka percaya pada hari kiamat, dan berusaha menyatukan ajaran Islam, Kristen dan Yahudi, sehingga memberi dampak yang besar kepada masyarakat awam. Pendapat-pendapat mereka didasarkan kepada ayat-ayat al-Qur’an dengan pemahamanan yang meyimpang. Artikel ini mencoba menelaah bagaimana penyimpangan dalam penafsiran al-Qur’an yang dilakukan oleh kelompok Millah Ibrahim dan bagaimana dampak penyimpangan tersebut terhadap masyarakat Johor. Hasil penelitian menunjukkan bahwa penyimpangan penafsiran yang dilakukan oleh kelompok Millah Ibrahim terlihat dalam surat al-Maidah ayat 68, surat al-Baqarah ayat 22, al-Ankabut ayat 45, dan al-Hijir ayat 87. Penyimpangan tersebut pada umumnya terjadi karena kurang terpenuhinya syarat-syarat untuk menjadi seorang mufasir. Dampak dari penyimpangan tersebut, dimana masyarakat awam di Johor termakan oleh penjelasan-penjelasan yang disampaikan oleh kelompok ini. Kelompok ini menjelaskan bahwa apa yang dimaksud dengan hari kiamat yang disebut dalam al-Qur’an bukanlah hari dimana dunia ini hancur dan kemudian jin dan manusia dibangkitkan kembali, tetapi yang mereka maksud adalah hari kebangkitan agama.